IMPROVING STUDENTS’ ABILITY IN READING COMPREHENSION THROUGH QUESTION ANSWER RELATIONSHIP (QAR) AT THE EIGHTH GRADE OF SMP N 1 PONDIDAHA - Wahyudi, Iin (Aksara Public, 2019)
This study was aimed to find out the improvement of students’ ability in reading comprehension by using question answer relationship strategies in grade VIII SMP N 1 Pondidaha. The subject of this study was grade VIII SMP N 1 Pondidaha. It was consisted of 38 students. This research applied by Class Room Action Research. The technique of analyzing data of this research was applied by using descriptive technique. The qualitative data was taken from diary notes, interview, and observation sheet. The quantitative data was taken from the test. The result in pre-observation showed that there were 11 students who got the standard of achievement namely ≥ 70 (the rule from school) with the percentage of score 44%. While in the first cycle was improved became 17 students who got the standard of achievement (≥ 70) with the percentage of score was 63%. And in the second cycle was improved 24 who got the standard of achievement (≥ 70) with the percentage of score was 88% and in the second cycle was improved 24 who got the standard of achievement (≥ 70) with the percentage post test was 92 %. There was an improving of students’ reading achievement related to the target achievement of this research, namely 80% of them got standard score ≥ 70. It’s related to the result of observation showed that the students were more interested and motivated in joining the class and they were enthusiastic during teaching learning process.